2021
DOI: 10.1038/s41598-020-79703-2
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal mice resist Plasmodium yoelii infection until exposed to para-aminobenzoic acid containing diet after weaning

Abstract: We developed a newborn (NB) mouse Plasmodium yoelii NL infection model to study malaria in early age. Surprisingly, the onset of parasitemia in P. yoelii challenged NB mice was delayed compared to adults and coincided with the weaning date when weanlings switched from maternal milk to normal chow diet. Also, compared to adult mice, parasitemia resolved much later (48 days vs 20 days post challenge) and the peak parasitemia was twice as high in weanlings. Concurrently, weanlings’ germinal center reaction was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(73 reference statements)
1
2
0
Order By: Relevance
“…In agreement with this, earlier work reported that pABA-deficient diets in rodent hosts is responsible for poor parasite growth and infection, indicating that pABA is an essential host-derived nutrient [10][11]. Indeed, newborn mice on naturally pABA-deficient milk diets suppressed parasitemia with Py17XNL infection and removal of pABA from the rodent diet reduced parasite load [12]. Therefore, it is notable that pABA is present in normal laboratory mouse feed at levels that allow for asexual blood stages to progress without additional supplementation (~175 ug/kg in conventional mouse feed) [9].…”
Section: Introductionsupporting
confidence: 69%
“…In agreement with this, earlier work reported that pABA-deficient diets in rodent hosts is responsible for poor parasite growth and infection, indicating that pABA is an essential host-derived nutrient [10][11]. Indeed, newborn mice on naturally pABA-deficient milk diets suppressed parasitemia with Py17XNL infection and removal of pABA from the rodent diet reduced parasite load [12]. Therefore, it is notable that pABA is present in normal laboratory mouse feed at levels that allow for asexual blood stages to progress without additional supplementation (~175 ug/kg in conventional mouse feed) [9].…”
Section: Introductionsupporting
confidence: 69%
“…Exclusive (but not necessarily partial) breastfeeding has been suggested to reduce the risk of P. falciparum infection in neonates and young infants from the Gambia, 2 most likely because maternal milk is deficient in para-aminobenzoic acid, which is required for de novo folate synthesis by malaria parasites. 32,33 More recent evidence that exclusive breastfeeding protects infants from clinical malaria comes from a birth cohort study in Malawi 34 and cross-sectional surveys in the Democratic Republic of Congo 35 and Cameroon, 36 all in Sub-Saharan African settings where P. falciparum is the dominant human malaria parasite.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, earlier work reported that pABA-deficient diets in rodent hosts are responsible for poor parasite growth and infection, indicating that pABA is an essential host-derived nutrient ( 10 , 11 ). Indeed, newborn mice on naturally pABA-deficient milk diets suppressed parasitemia with Py17XNL infection and removal of pABA from the rodent diet reduced parasite load ( 12 ). Therefore, it is notable that pABA is present in normal laboratory mouse feed at levels that allow for asexual blood stages to progress without additional supplementation (~175 μg/kg of body weight in conventional mouse feed) ( 9 ).…”
Section: Introductionmentioning
confidence: 99%